2009
DOI: 10.1074/jbc.m109.010017
|View full text |Cite
|
Sign up to set email alerts
|

House Dust Mite Allergen Der f 2-induced Phospholipase D1 Activation Is Critical for the Production of Interleukin-13 through Activating Transcription Factor-2 Activation in Human Bronchial Epithelial Cells

Abstract: The purpose of this study was to identify the role of phospholipase D1 (PLD1) in Der f 2-induced interleukin (IL)-13 production. The major house dust mite allergen, Der f 2, increased PLD activity in human bronchial epithelial cells (BEAS-2B), and dominant negative PLD1 or PLD1 siRNA decreased Der f 2-induced IL-13 expression and production. Treatment of Der f 2 activated the phospholipase C␥ (PLC␥)/protein kinase C␣ (PKC␣)/p38 MAPK pathway. Der f 2-induced PLD activation was attenuated by PLC␥ inhibitors (U73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…Overexpression of catalytically inactive mutants of PLD attenuates LPA-induced IL-13Ralpha2 gene expression and protein secretion (Zhao et al, 2007). House dust mite allergen Derf2-induced PLD1 activation is critical for IL-13 production (Park et al, 2009). However, the involvement of PLD in CSE-induced inflammation responses has not been well described.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overexpression of catalytically inactive mutants of PLD attenuates LPA-induced IL-13Ralpha2 gene expression and protein secretion (Zhao et al, 2007). House dust mite allergen Derf2-induced PLD1 activation is critical for IL-13 production (Park et al, 2009). However, the involvement of PLD in CSE-induced inflammation responses has not been well described.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous reports have shown that PLD is regulated via PLC in rat alveolar macrophages (Cha et al, 1998), via PKC in peripheral blood mononuclear cells (Oh et al, 2000) and T cells from Dermatophagoides farinae-allergic individuals (Oh et al, 2004) and via a PLC/PKC/p38MAPK pathway in BEAS-2B cells (Park et al, 2009). To further elucidate the relevance of a PLC/ PKC/p38MAPK pathway in CSE-induced PLD1 and IL-6 expressions, BEAS-2B cells were pretreated with PAO (PLC inhibitor), Go6976 (PKC inhibitor), and SB203580 (p38MAPK inhibitor) for 30 min prior to being treated with CSE for 1 hr and harvested.…”
Section: Effect Of Gi Protein Plc Pkc and P38mapk Inhibitors On Csementioning
confidence: 99%
See 3 more Smart Citations